Operationalizing and measuring individual entrepreneurial orientation using cognitive mapping and MCDA techniques - Ferreira, F. A. F. (2016)
Despite the widely acknowledged importance of entrepreneurial orientation in the establishment of successful ventures, identifying entrepreneurship attitudinal orientation, and finding its determinants in particular, is a complex undertaking due to the variety of intuition- or subjectivity-based factors underlying individual entrepreneurial orientation (IEO). Grounded on the integrated use of cognitive maps and the measuring attractiveness by a categorical-based evaluation technique (MACBETH), this paper aims to develop a multiple criteria decision analysis (MCDA) framework to assist the measurement of IEO. This evaluation mechanism makes it possible to classify individuals according to their entrepreneurial profiles, allowing managers and investors to make more informed decisions regarding business partnerships or funding allocations. Specific guidelines on how to construct such a mechanism, implications for scholars and practitioners, as well as the strengths and shortcomings of our measurement system, are also discussed.